Fibrodysplasia Ossificans Progressiva – a presentation of cases and literature review - Dąbrowska, Małgorzata; Dąbrowski, Piotr; Tabarkiewicz, Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. Fibrodysplasia ossificans progressiva (FOP) is a very rare inherited disease leading to progressive ectopic ossification of muscle and soft tissue and resulting in severe immobilisation and premature death. The mutations in ACVR1 gene that codes the 1A activin receptor which belongs to the family of bone morphogenetic proteins (BMPs) are leading to clinical symptoms. Aim. In this raport we present 3 cases of paediatric FOP patients presenting varied clinical course of disease. Description of the cases. Case 1. A girl, currently 5 years old, was hospitalised for the first time at the age of 10 months with suspicion of a hyperplastic lesion of the left lumbar area. The time period between the first symptom, i.e. subcutaneous oedema, and the correct diagnosis was about 8 months. The symptom with key importance for the diagnosis was congenital deformities of the thumbs and big toes. Case 2. A 6-year-old girl with a congenital hallux valgus in both feet, a small painless nodular lesion in the area of the distal metaphysis of the femur, limiting the flexion of the knee joint, was diagnosed in the third month of life. Case 3. A three-year-old girl was diagnosed with congenital defects i.e. hallux valgus of both feet. The first symptoms of the disease occurred during her 14th month when an oedema of the subcutaneous tissue of the nape area was observed. Conclusion. Until recently, there has been no efficient therapy which could slow down the natural course of the disease and currently the disease is treated as incurable. Of key importance from the perspective of patients is early diagnosis and, more importantly, preventing traumas, surgical procedures, intramuscular injections, sparing dental treatment and ensuring avoidance of airway tract infections.
The authors thank prof. Frederick Kaplan (The Isaac & Rose Nassau Professor of Orthopaedic Molecular Medicine and Chief of the Division of Molecular Orthopaedic Medicine at the University of Pennsylvania School of Medicine) for inspirations, directions and discussion during writing this article. The authors thank prof. David Aebisher for his help in text editing and English corrections.
Keywords: clinical course; diagnostic difficulties; ectopic ossification; fibrodysplasia ossificans progressiva